Compact dual polarized aperture coupled microstrip patch antenna for UWB RFID applications. Issue 6 (30th March 2017) - Sethi, Waleed Tariq; AlShareef, Mohammed R.; Ashraf, M.; Behairy, Hatim M.; Alshebeili, S.
ABSTRACT: This letter presents the design and realization of a compact dual polarized aperture coupled microstrip patch antenna for ultra‐wideband radio frequency identification (UWB‐RFID) applications. The antenna occupies relatively small volume (30 × 30 × 6.7 mm 3 ), hence offers more space for ease of integration with other components. The antenna achieves dual polarization by utilizing two symmetric coupling apertures that excite two orthogonal modes. The dual feed portions are placed on a Rogers R04360 substrate, while the square patches are deposited onto Rogers RT‐5880 substrate layers. The antenna is designed to operate in the frequency range of 6–8 GHz. The realized antenna at the center frequency of 7 GHz achieves a dual‐polarized broadside radiation pattern having a high gain of 7.57 and 7.69 dBi at port‐1 and port‐2, respectively. It also achieves fractional bandwidths of 24 and 32% at port‐1 and port‐2 while maintaining high port isolation of more than 25 dB. The findings are very promising for UWB‐RFID applications. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:1317–1321, 2017